2021
DOI: 10.1097/cmr.0000000000000726
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the IL-2 inducible kinase in melanoma; a phase 2 study of ibrutinib in systemic treatment-refractory distant metastatic cutaneous melanoma: preclinical rationale, biology, and clinical activity (NCI9922)

Abstract: Background IL-2 inducible kinase (ITK) is highly expressed in metastatic melanomas and its inhibition suppresses melanoma cell proliferation. We hypothesize that ibrutinib has a direct antitumor effect in melanoma cell lines and that treatment of metastatic melanomas with ibrutinib induces antitumor responses. Methods We assessed the ibrutinib effect on melanoma cell proliferation, apoptosis, and motility. Patients with metastatic melanoma refractory to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…These two closely associated genes both showed up in our model of predicting responses/prognoses, suggesting that IL-2-related pathways and the function of macrophages are important in melanoma. But the application of ibrutinib, a drug that targets IL-2 inducible kinase (which is highly expressed in melanoma), did not deliver any clinical benefits in patients with metastatic melanoma whose PD-1 treatment was failed [ 49 ]. Our model provided more insights into this by revealing another inflammation-related gene indicative of immunotherapy response and closely related to the prognosis: PTAFR.…”
Section: Discussionmentioning
confidence: 99%
“…These two closely associated genes both showed up in our model of predicting responses/prognoses, suggesting that IL-2-related pathways and the function of macrophages are important in melanoma. But the application of ibrutinib, a drug that targets IL-2 inducible kinase (which is highly expressed in melanoma), did not deliver any clinical benefits in patients with metastatic melanoma whose PD-1 treatment was failed [ 49 ]. Our model provided more insights into this by revealing another inflammation-related gene indicative of immunotherapy response and closely related to the prognosis: PTAFR.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the promising data presented here, recently, a phase II single-arm clinical trial involving 18 patients with metastatic melanoma refractory to PD-1 and MAPK inhibitors did not find an effective antitumor response to the use of Ibrutinib. The authors discuss the reported outcome as a possible consequence of the combination of several factors, including the ability of Ibrutinib to inhibit ITK, the relevance of this target for the treatment of melanoma, and the administered dose (840 mg daily) used to treat solid tumors such as melanoma [36]. Although the result seems disappointing, the authors suggest that additional research is needed to better characterize the Ibrutinib's mechanisms of action in different types of melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, preliminary clinical data of several trials show no or limited clinical benefit of ibrutinib and acalabrutinib at improving the objective response rates (ORRs), progression-free survival (PFS) or overall survival (OS) in patients with several solid tumors (Table 2). These include ibrutinib plus durvalumab in R/R non-small cell lung cancer (NSCLC), breast cancer and pancreatic cancer (NCT02403271); acalabrutinib in recurrent glioblastoma (NCT02586857); ibrutinib in refractory metastatic cutaneous melanoma (NCT02581930) (52); acalabrutinib in combination with pembrolizumab in advanced head and neck squamous cell carcinoma (HNSCC) (NCT02454179), non-small cell lung cancer (NCT02448303) and platinum-refractory metastatic urothelial carcinoma (NCT02351739) (55); acalabrutinib alone or in combination with pembrolizumab in refractory ovarian cancer (NCT02537444) and metastatic or locally advanced unresectable pancreatic ductal adenocarcinoma (NCT02362048) (53); ibrutinib in combination with Nab-paclitaxel and gemcitabine in metastatic pancreatic cancer (NCT02436668) and (NCT02562898) (54); and ibrutinib alone in advanced carcinoid and pancreatic neuroendocrine tumors (Table 2) (www.clinicaltrials.com). Nonetheless, peripheral reductions in MDSCs and increases in proliferating CD8 T cell subsets are observed in some of these cases (53,55).…”
Section: Hematological Malignancies Of Myeloid Cells and T Cellsmentioning
confidence: 99%